THE PHENOMENON OF PARENTAL INVOLVEMENT IN THE PEDAGOGICAL PROCESS - Makhmudova , Gulnora; Makhmudkhodjaev , Orifkhuja (MMIT Proceedings, 2023)
This thesis is devoted to the disclosure of the problems of the role of parents in the pedagogical process. The essence of the work lies in the fact that the practice of involving parents in making managerial decisions on the education of their children and organizing research to take into account parental opinion is gradually becoming more important and popular, but it is not yet mass and therefore it is possible to face some problems in matters of equal interaction in the educational process of parents on an equal basis with teachers.